2001
DOI: 10.1002/1521-3919(20010401)10:4<389::aid-mats389>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Microphase Separation within a Comb Copolymer with Attractive Side Chains: A Computer Simulation Study

Abstract: Computer simulation modelling of a flexible comb copolymer with attractive interactions between the monomer units of the side chains is performed. The conditions for the coil‐globule transition, induced by the increase of attractive interaction, ε, between side chain monomer units, are analysed for different values of the number of monomer units in the backbone, N, in the side chains, n, and between successive grafting points, m. It is shown that the coil‐globule transition of such a copolymer corresponds to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…An interesting competition between the behavior of the flexible side chains and the (typically) much stiffer backbone under poor-solvent conditions must be expected. In addition, just as for polymer brushes on flat substrates the interplay between grafting density σ and side chain length N causes lateral segregation between dense "clusters" rather than uniform collapse in some intermediate regime under poor-solvent conditions [33][34][35], similar lateral microphase separation along the backbone of a bottlebrush can be expected [36,37]. Apart from qualitative scaling predictions for the phase diagram that one should expect for the bottlebrush [36] and qualitative observations for a lattice model with very short side chains (up to N = 12 only [37]), this type of lateral microphase separation in bottlebrushes has not yet been characterized.…”
mentioning
confidence: 86%
“…An interesting competition between the behavior of the flexible side chains and the (typically) much stiffer backbone under poor-solvent conditions must be expected. In addition, just as for polymer brushes on flat substrates the interplay between grafting density σ and side chain length N causes lateral segregation between dense "clusters" rather than uniform collapse in some intermediate regime under poor-solvent conditions [33][34][35], similar lateral microphase separation along the backbone of a bottlebrush can be expected [36,37]. Apart from qualitative scaling predictions for the phase diagram that one should expect for the bottlebrush [36] and qualitative observations for a lattice model with very short side chains (up to N = 12 only [37]), this type of lateral microphase separation in bottlebrushes has not yet been characterized.…”
mentioning
confidence: 86%
“…12 We also note that it is of great interest [1][2][3][4][13][14][15][16][17][18][19] to consider the extension of the model to two chemically different types of side chains, 20 but such an extension will be disregarded, as well as effects due to backbone flexibility. 21,22 We hope, however, to report on such extensions in future studies. Whereas under good solvent conditions for large grafting density it can be shown that the local structure in a polymer bottle-brush with flexible backbone is almost indistinguishable from a rigid backbone case, 23 different properties must be expected under conditions where the "pearl-necklace" structure formation is possible.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, it has recently been shown that the persistence length depends not onlyon the backbone length [19,20], but on the solvent conditions as well [15]. Although there exist many experimental and theoretical studies for the linear d imensions of these macro molecules in various solvents [3,4,19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36],there are very few systematic studies of this problem [15], wherethe power laws and the associated effective exponents have been with a Flexible Backbone under Theta and Good Solvent Conditions discussed.It has been shown that for bottle brushes with a flexib le backbone evenat the theta point the side chains are considerably stretched,their linear dimension depending on the solvent quality only weakly, whilethe dependence of the persistence length on backbone length and temperature has alsobeen discussed [15].…”
Section: Introductionmentioning
confidence: 99%